SYNTHESIS OF NANO HYDROXYAPATITE CERAMIC POWDERS USING DIFFERENT SURFACTANT TEMPLATES AND THEIR CHARACTERIZATION - Amin, S.; Anjum, A. D.; Siddique, T.; Shah, S. S.; Mujahid, M. (The Nucleus, 2010)
In the present study synthesis of nano hydroxyapatite; HA, Ca10(PO4)6(OH)2 using different surfactants as templates are exploited. Three surfactants such as Cetyl Trimethyl Ammonium Bromide; CTAB (cationic), Sodium Dodecyl Sulphate; SDS (anionic) and Polyoxyethylene sorbitane monolaurate; Tween 20 (nonionic) surfactants have been used as nano reactors for the synthesis of hydroxyapatite ceramic powders. Precipitation route has been used for synthesis with same calcium and phosphate precursors. The effect of different templates on the synthesis, morphology and particle size has been investigated. Considerable influence of templates on the morphology and particle size of the synthesized HA is observed. The samples are characterized using XRD, FTIR and SEM to evaluate the quality, morphology and particle size. The chemical and structural compositions of the products are examined by FTIR. SEM micrographs reveal a rod like structure of HA; possessing various thickness and length in nano range; vary in contrast of each template while the XRD spectra show some other minor phases alongwith HA.